Patient Satisfaction with Outpatient Pharmaceutical Services Under the National Health Insurance Scheme in Indonesia: A Cross-Sectional Study - Hurit, Hermanus Ehe; Putri, Andini Adinda; Bachri, Nurjannah (Chakra Brahmanda Lentera Institute, 2026)
Background: The utilization of Indonesia’s National Health Insurance Scheme has increased. However, evidence on patient satisfaction with pharmaceutical services under national health insurance schemes in low- and middle-income countries, particularly using the SERVQUAL framework, remains limited. This gap is important, as Indonesia’s National Health Insurance Scheme patient characteristics may shape perceptions of service quality and inform targeted service improvement strategies. This study aimed to analyze the relationship between Indonesia’s National Health Insurance Scheme patient characteristics and satisfaction with outpatient pharmaceutical services. Methods: A quantitative cross-sectional study was conducted and reported in accordance with the STROBE guidelines. The study involved Indonesia’s National Health Insurance Scheme outpatients at the Pharmacy Installation of Dr. Suyoto Hospital, Jakarta, in 2023, who met the inclusion criteria (aged ≥18 years, received pharmaceutical services, and provided informed consent). Data were collected using a SERVQUAL questionnaire assessing five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Patient characteristics (gender, age, education, and occupation) were analyzed as independent variables, while satisfaction served as the dependent variable. Associations were examined using Spearman’s rank correlation test. Results: Significant and strong correlations were found between patient satisfaction and age (ρ = 0.71; p < 0.001) as well as education level (ρ = 0.70; p < 0.001). Gender and occupation demonstrated statistically significant but weak associations with satisfaction. Conclusion: Satisfaction with outpatient pharmaceutical services among Indonesia’s National Health Insurance Scheme patients is significantly associated with specific demographic characteristics, particularly age and education. These findings underscore the importance of patient-centered service improvement strategies, with an emphasis on enhancing responsiveness and pharmaceutical communication to improve the quality of Indonesia’s National Health Insurance Scheme services sustainably.